2002
DOI: 10.1037/0012-1649.38.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

Statistical regularities in vocabulary guide language acquisition in connectionist models and 15-20-month-olds.

Abstract: This research tested the hypothesis that young children's bias to generalize names for solid objects by shape is the product of statistical regularities among nouns in the early productive vocabulary. Data from a four-layer Hopfield network suggested that the statistical regularities in the early noun vocabulary are strong enough to create a shape-bias, and that the shape-bias is overgeneralized to non-solid stimuli. A second simulation suggested this overgeneralization is due to the dominance of names for sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
229
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(247 citation statements)
references
References 50 publications
16
229
1
Order By: Relevance
“…In contrast, material bias results aren't so stable: two-and two-and-a-half-yearolds showed material bias (Soja et al, 1991); so did three-, four-, and five-year-olds (Dickinson, 1988); meanwhile, toddlers ranging from 17 to 33 months old never showed material bias (Samuelson & Smith, 1999); two-, two-and-a-half-, and four-year-olds and adults who spoke Japanese and two-year-olds who spoke English showed material bias, but two-and-a-half-, four-year-olds, and adults who spoke English didn't (Imai & Gentner, 1997); three-, four-, and five-year-olds didn't show material bias when given such syntax information as determiners (Subrahmanyam, Landau, & Gelman, 1999). And surprisingly, Samuelson (2002) reported that children showed extraordinary shape bias for nonsolid stimulus, which is the exact opposite case of material bias. Here, we call such opposite bias "overgeneralized shape bias" because it looks like the overgeneralization of shape bias to material bias.…”
Section: Summary Of Findings About Wordmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, material bias results aren't so stable: two-and two-and-a-half-yearolds showed material bias (Soja et al, 1991); so did three-, four-, and five-year-olds (Dickinson, 1988); meanwhile, toddlers ranging from 17 to 33 months old never showed material bias (Samuelson & Smith, 1999); two-, two-and-a-half-, and four-year-olds and adults who spoke Japanese and two-year-olds who spoke English showed material bias, but two-and-a-half-, four-year-olds, and adults who spoke English didn't (Imai & Gentner, 1997); three-, four-, and five-year-olds didn't show material bias when given such syntax information as determiners (Subrahmanyam, Landau, & Gelman, 1999). And surprisingly, Samuelson (2002) reported that children showed extraordinary shape bias for nonsolid stimulus, which is the exact opposite case of material bias. Here, we call such opposite bias "overgeneralized shape bias" because it looks like the overgeneralization of shape bias to material bias.…”
Section: Summary Of Findings About Wordmentioning
confidence: 99%
“…Linda Smith and colleagues led LBA studies (Smith, 1995;Samuelson & Smith, 1999;Smith, Jones, Landau, Gershkoff-Stowe, & Samuelson, 2002;Samuelson, 2002;Colunga & Smith, 2005). They have explained word learning biases by associative learning.…”
Section: Previous Lba Studiesmentioning
confidence: 99%
See 3 more Smart Citations